2014
DOI: 10.1021/bm500647n
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibrils Enhance Transport of Metal Nanoparticles in Living Cells and Induced Cytotoxicity

Abstract: Amyloid protein fibrils occur in vivo as pathological agents, in the case of neurodegenerative diseases, or as functional amyloids, when playing biologically vital roles. Here we show how amyloid fibrils generated from a food protein, β-lactoglobulin, can be used as nanoreactors for the synthesis of metal nanoparticles and demonstrate that the resulting hybrids can play a central role in the internalization of nanoparticles into living cells, with up to 3-fold-enhanced transport properties over pristine nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…Shortly after this work, another amyloid system based on the non‐toxic β‐lactoglobulin, was shown to enhance transport of metal nanoparticles in living cells . The authors used two types of cells, a cell line and dendritic cells, to demonstrate that the same gold nanoparticles penetrate with a three‐fold stronger efficiency when conjugated to amyloid fibrils compared to bare nanoparticles.…”
Section: Functional Amyloid In Technological Applicationsmentioning
confidence: 99%
“…Shortly after this work, another amyloid system based on the non‐toxic β‐lactoglobulin, was shown to enhance transport of metal nanoparticles in living cells . The authors used two types of cells, a cell line and dendritic cells, to demonstrate that the same gold nanoparticles penetrate with a three‐fold stronger efficiency when conjugated to amyloid fibrils compared to bare nanoparticles.…”
Section: Functional Amyloid In Technological Applicationsmentioning
confidence: 99%
“…In contrast, β-lactoglobulin (bLg) is a natural whey protein which hydrolyzes into small peptide fragments upon heating and acid exposure (pH 2), and subsequently self-assembles into functional bLg amyloid fibrils. 7, 8 Efficient in vitro iron delivery and wastewater purification have been recently demonstrated using bLg amyloids, 9, 10 pointing to the untapped potential of this biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…10 For instance, Bolisetty et al generated amyloid fibrils from b-lactoglobulin, and found that their conjugation to metal nanoparticles enhanced cell permeability and toxicity. 11 Haratifar et al used tea catechin-casein complex to significantly decrease cancer cell proliferation. 12 However, these approaches were not subjected to in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%